Crop diversification in lower Nyando - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
The CGIAR research program on Climate Change, Agriculture and Food Security (CCAFS) East Africa, Kenya Agriculture Research Institute (KARI) and the Ministry of Agriculture are working with farmers to support crop diversification to manage climate risk and to enhance resilience to climate change. Photos: K. Trautmann.